North Africa Coastal Cities Address Natural Disasters and Climate Change - World Bank (Washington, DC, 2014)
North Africa's coastal cities, long benefitting from their ready access to commerce and culture, also face distinct vulnerabilities due to their location. Natural hazards and extreme weather patterns impose risks on coastal areas that inland areas seldom encounter. North Africa's increasingly populous cities face tangible risks today, but these will be amplified as the impacts of global climate change further manifest themselves over the decades to come. The study, 'climate change adaptation and natural disasters preparedness in the coastal cities of North Africa,' analyzed the exposure of all four locations to natural disasters, such as floods and storm surges, earthquakes and tsunamis, as well as to the increasingly frequent weather extremes associated with climate change. The project, which has taken place from June 2009 to June 2011, has provided tools for evaluating the risks, costing out potential losses, and moving toward specific reforms and investments designed to adapt the cities to a changing climate and increase their resilience to natural hazards.